FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL DALAM SEKTOR INDUSTRI BARANG KONSUMSI - ANGGUNMULIA, SINTIA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Capital structure is interesting to be studied because it can provide overview for managers in making a decision for the company to address the problem - a problem that occurs in the company, with the factors that influence the capital structure under study is the asset structure, firm size, Profitability. This study aims to determine influence asset structure, firm size, capital structure and profitability of the consumer goods industry. This study used a sample of the consumer goods industry enterprises period 2006-2010 and the sample used amounted to 28 companies. The results of this study indicate that the structure of assets and company size has a positive effect on capital structure in the industrial sector of consumer goods but not significant. Profitability and a significant negative effect on capital structure in the consumer goods industry.